Perceptions of Electronic Health Records Within Otolaryngology Residents Compared to Practicing Otolaryngologists. (8th September 2018) - Harrill, Peter A.; Melon, David E.; Seshul, Merritt J.; Zanation, Adam
Abstract : Objective: This study investigated the perceived impact of electronic health records (EHR) on otolaryngology residents with regard to education, patient care, and workflow, and then compared the trends with those of practicing otolaryngologists. Methods: A descriptive, cross‐sectional survey was developed for each core study group: the otolaryngology resident group (ORG) and the practicing otolaryngologist group (POG). In total, 536 surveys were submitted: 33 from the ORG survey and 510 from the POG survey. Response rates were 51.5% and 21.3%, respectively. Results: Within the two study groups, ORG reported a predominately neutral response relating to the impact of EHR on experience compared with the POG, which reported far more negative responses. The most negative reported change in the ORG related to feeling more like a passive observer and scribe in terms of how EHR negatively impacted the role of resident. Within the POG group, the majority of negative responses were recorded on the impact of EHR on practice efficiency, practice overhead, and number of employees required to maintain practice function. Conclusion: With otolaryngologists making up 1.1% of the U.S. physician workforce in 2015, it is likely that software programing of EHR underrepresents the workflow needs of otolaryngologists at this time. Future studies investigating the impact of EHR on otolaryngology patient care and resident education are needed in the future. Laryngoscope, 128:2726–2731, 2018